A Cell-Free Content Mixing Assay for SNARE-Mediated Multivesicular Body-Vacuole Membrane Fusion - Karim, Mahmoud Abdul; Samyn, Dieter Ronny; Brett, Christopher Leonard (Methods in molecular biology (Clifton, N.J.), 2019)
Endocytosis is a fundamental process underlying diverse eukaryotic physiology. The terminal stage of this process is membrane fusion between the perimeter membrane of a late endosome filled with intraluminal vesicles, or multivesicular body (MVB), and the lysosome membrane to facilitate catabolism of internalized biomaterials or surface polytopic proteins. To comprehensively understand the mechanisms underlying MVB-lysosome membrane fusion, we developed a quantitative, cell-free assay to study this SNARE-mediated event in molecular detail using Saccharomyces cerevisiae and its vacuolar lysosome, or vacuole, as models. This involves separately isolating organelles from two yeast strains each expressing a different complementary fusion probe targeted to the lumen of either MVBs or vacuoles. Isolated organelles are mixed in vitro under fusogenic conditions. Upon MVB-vacuole membrane fusion, luminal contents mix to facilitate probe interaction, reconstituting β-lactamase activity recorded by a colorimetric enzyme activity assay. This method accommodates a multitude of approaches (e.g., genetics, addition of purified protein reagents) to study this process in isolation, and in theory could be repurposed to study other SNARE-mediated fusion events within cells.